THE INFLUENCE OF COMMUNITY EDUCATION LEVELS ON POLITICAL PARTICIPATION IN PUJANANTING DISTRICT, BARRU REGENCY - A.Pananrangi M; Herlina Amriana; MukminMuhammad; Nurul Hariani (Jurnal Scientia, 2023)
This research aims to determine the influence of community education level on community political participation and the factors that influence community political participation in Pujananting District, Barru Regency. Data sources were obtained by means of questionnaires, interviews, observations. The data analysis method used is parametric inferential statistical techniques (Regression Analysis-SPSS). The results of research using SPSS show that the level of public education on political participation in Pujananting District does not have a significant effect where the results of the simultaneous Hypothesis test (F test) and T test (partial) show a significance of <0.05, namely 0.156 and the factors that influence political participation society is the level of knowledge, community work, the role of government officials, the influence of intellectuals and conflicts of interest between political leaders.